NEW ONSET GRAVES’ DISEASE AFTER SARS-CoV-2 VACCINATION - Chiew, Ken Seng; Khaw, Chong Hui; Velaiutham, Shanty (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND There are increasing number of reports of thyroid dysfunction after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination. We report a case of new-onset Graves’ disease following vaccination with adenovirus-vectored Vaxzevria (Oxford-AstraZeneca). CASE A 29-year-old female with no prior history of endocrine or autoimmune disease presented with a week of palpitations, heat intolerance and excessive sweating starting three days after her second dose of Vaxzevria. She was asymptomatic after her first dose given two months earlier. Her father and sister have Graves’ disease. She had a diffuse goitre and no orbitopathy. Tests showed suppressed TSH [<0.01 mIU/L, normal range (NR) 0.27-4.2], elevated free T4 (>100 pmol/L, NR 12-22) and positive TSH receptor antibody (>40.00 IU/L, NR <1.75). Ultrasonography revealed a hypervascular, diffusely enlarged goitre. Oral carbimazole and propranolol were commenced. Five months later, free T4 normalized and TSH remained undetectable. To date, she remains hesitant to receive her booster dose. SARS-CoV-2 infection and vaccination have been asso- ciated with subacute thyroiditis and autoimmune thyroid disease. While there are reports of new-onset Graves’ disease after mRNA and adenovirus-vectored vaccines, it has not been associated with inactivated virus vaccines. The prevailing postulation is that the adjuvants in the vaccines can trigger an autoimmune event. CONCLUSION Physicians should be aware of the possibility of thyroid dysfunction after SARS-CoV-2 vaccination, especially in those with strong family history. More studies are required to establish causal relationship.